2020
DOI: 10.1038/s41564-020-0737-6
|View full text |Cite
|
Sign up to set email alerts
|

A nutrient-limited screen unmasks rifabutin hyperactivity for extensively drug-resistant Acinetobacter baumannii

Abstract: Industry screens of large chemical libraries traditionally have relied on rich media to ensure rapid bacterial growth in high-throughput testing. We used eukaryotic, nutrient-limited growth media in a compound screen that unmasked a previously unknown hyper-activity of the old antibiotic, rifabutin (RBT), against highly resistant Acinetobacter baumannii . In nutrient-limited, but not rich media, RBT was 200-fold more potent than rifampin (RIF). RBT was also substantially more effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 32 publications
3
68
0
Order By: Relevance
“…Doses >900 mg/d were not associated with further increases in Cmax, ranging from 0.4 µg/mL to 1 µg/mL [ 23 , 24 ]. Although its Cmax is low, the rifabutin MICs of most A. baumannii strains tested in nutrient-depleted media were <0.1 µg/mL [ 4 ], readily exceedable by standard rifabutin dosing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Doses >900 mg/d were not associated with further increases in Cmax, ranging from 0.4 µg/mL to 1 µg/mL [ 23 , 24 ]. Although its Cmax is low, the rifabutin MICs of most A. baumannii strains tested in nutrient-depleted media were <0.1 µg/mL [ 4 ], readily exceedable by standard rifabutin dosing.…”
Section: Methodsmentioning
confidence: 99%
“…We recently found that rifabutin possesses hitherto unknown hyperactivity against most strains of A. baumannii [ 4 ]. Rifabutin, which has been approved for use in humans for >30 years, has minimal inhibitory concentrations (MICs) against A. baumannii strains that are >50-fold below those of rifampin.…”
mentioning
confidence: 99%
“…Transposon mutant libraries demonstrate their versatility in the foundation of studies and as demonstrated by Luna et al (2020) can be repurposed years in the future to investigate and validate novel findings.…”
Section: High-throughput Genetic Screening Transposon Mutagenesismentioning
confidence: 99%
“…To ensure that unnecessary selection pressures are avoided, freezing of the pooled mutants must occur very shortly after selection ( Kazi et al, 2020 ). However, as research progresses, storing and exposing strains of interest to new conditions/stress allows investigation of novel effects as demonstrated for an XDR clinical lung isolate HUMC1 ( Luna et al, 2020 ). The authors repurposed a previously generated mutant library in AB5075 in order to validate results observed in HUMC1 ( Gallagher et al, 2015 ).…”
Section: High-throughput Genetic Screeningmentioning
confidence: 99%
See 1 more Smart Citation